2023
DOI: 10.1097/xcs.0000000000000553
|View full text |Cite
|
Sign up to set email alerts
|

Low vs Standard-Dose Indocyanine Green in the Identification of Biliary Anatomy Using Near-Infrared Fluorescence Imaging: A Multicenter Randomized Controlled Trial

Abstract: BACKGROUND: Near-infrared fluorescence imaging using intravenous indocyanine green (ICG) facilitates intraoperative identification of biliary anatomy. We hypothesize that a much lower dose of ICG than the standard decreases hepatic and background fluorescence and improves bile duct visualization. STUDY DESIGN: In this multicenter randomized controlled trial, 55 adult patients undergoing laparoscopic cholecystectomy were randomized to low-dose (0.05 mg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…They found that the tumors that were not identified intraoperatively through the technique were significantly smaller (11 mm vs. 18 mm, p = 0.019) and located deeper in the liver (10 mm vs 2 mm, p < 0.001), not identifying any of the tumors that were deeper than 8 mm from the liver surface [87]. This method can also be used to identify the bile duct [88], a structure that, if injured, causes intra-and postoperative complications, such as bile leak and biliary stricture (Figure 3) [89]. A recent study has shown that decreasing the ICG dose to 0.05 mg, instead of the standard 2.5 mg, preoperatively decreases hepatic and background fluorescence, allowing for a clear bile duct visualization within 15-20 min from administration [88].…”
Section: Visualization Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the tumors that were not identified intraoperatively through the technique were significantly smaller (11 mm vs. 18 mm, p = 0.019) and located deeper in the liver (10 mm vs 2 mm, p < 0.001), not identifying any of the tumors that were deeper than 8 mm from the liver surface [87]. This method can also be used to identify the bile duct [88], a structure that, if injured, causes intra-and postoperative complications, such as bile leak and biliary stricture (Figure 3) [89]. A recent study has shown that decreasing the ICG dose to 0.05 mg, instead of the standard 2.5 mg, preoperatively decreases hepatic and background fluorescence, allowing for a clear bile duct visualization within 15-20 min from administration [88].…”
Section: Visualization Techniquesmentioning
confidence: 99%
“…This method can also be used to identify the bile duct [88], a structure that, if injured, causes intra-and postoperative complications, such as bile leak and biliary stricture (Figure 3) [89]. A recent study has shown that decreasing the ICG dose to 0.05 mg, instead of the standard 2.5 mg, preoperatively decreases hepatic and background fluorescence, allowing for a clear bile duct visualization within 15-20 min from administration [88].…”
Section: Visualization Techniquesmentioning
confidence: 99%
“…The comparative analysis showed significantly lower The matched control group, without ICG-NIRF assistance, included nine boys with bilateral gynecomastia. The median patient's age at surgery was 14.6 years-old (range [12][13][14][15][16]. Five out of the nine patients (55.5%) developed postoperative seroma in the breast region, managed with needle aspiration in an outpatient setting (Clavien-Dindo 2).…”
Section: Preauricular Fistula and Second Branchial Cleft Fistulamentioning
confidence: 99%
“…The matched control group, without ICG-NIRF assistance, included five boys with a preauricular fistula. The median patient's age at surgery was 9.8 years-old (range [6][7][8][9][10][11][12][13][14]. Two out of the five patients (40%) developed postoperative complications, including surgical site infection and serous discharge from the surgical site, both managed with antibiotic therapy (Clavien-Dindo 2).…”
Section: Preauricular Fistula and Second Branchial Cleft Fistulamentioning
confidence: 99%
See 1 more Smart Citation